Asian medical students' attitudes towards professionalism. Issue 1 (1st January 2021) - Parthiban, Nirmalatiban; Boland, Fiona; Fadil Azim, Darlina Hani; Pawlikowska, Teresa; O'Shea, Marié T.; Jaafar, Mohamad Hasif; Morgan, Karen
ABSTRACT: Background: Professionalism is the basis of trust in patient–physician relationships; however, there is very limited evidence focusing on attitudes towards professionalism among medical students. Hence, the main aim of our study was to investigate Malaysian medical students' attitudes towards professionalism with specific emphasis on the comparison between pre-clinical and clinical students. Our secondary aim was to compare the differences in perception of medical students in Malaysia (pre-clinical and clinical) with Asian medical students studying in Dublin, Ireland Methods: This study utilized the Professionalism Mini-Evaluation Exercise (P-MEX) instrument which consists of 25 items that represent four skill categories: Doctor–Patient Relationship skills, Reflective skills, Time Management and Inter-Professional Relationship skills. Descriptive statistics were used to describe the demographic information of students and given the ordinal nature of the data, Mann–Whitney U-tests were used. Results: Overall, students have positive attitudes to all the professionalism items with more than 80% of the students agreeing that each of the professionalism attributes is important or very important. There was evidence of a significant difference between Malaysian pre-clinical and clinical students in relation to 'avoiding derogatory language' only (p = 0.015). When comparing between Malaysian and Dublin Asian students, there was a statistically significant difference in relation to 'show interest in patient as a person' (p < 0.003) for clinical students. Conclusion: Our results point to several curriculum implications such as 1) assessing students' attitudes towards professional attributes is essential when developing the professionalism curriculum, 2) integrating more effective clinical modules early in the curriculum and 3) considering geographical and cultural factors when assessing perception towards professional attributes.